Impact on health outcomes and productive work of adding anti-PD-1 agents to treat early-stage cancers in the United Kingdom: a modelling study - Burton, Hannah; Tan, Yan Zhi; Greenall, Sam; Neves, Catarina; Macdonald, Neil; Aguiar-Ibáñez, Raquel (Frontiers in Pharmacology, 2025)
BackgroundAnti-PD-1 agents are recommended in adjuvant or perioperative settings in some early-stage cancers. The health and productivity benefits of anti-PD-1 use on a population level, however, are unknown.MethodsA decision model was developed to quantify the health and productivity outcomes of adding anti-PD-1 agents to traditional management strategies in the adjuvant or perioperative setting for melanoma stage IIB/IIC/III, triple negative breast cancer, and renal cell carcinoma in the United Kingdom. The model consisted of four separate Markov models and compared outcomes in two scenarios: one where anti-PD-1 agents are restricted to advanced/metastatic disease, against one where anti-PD-1 agents are used as adjuvant or perioperative therapy for early-stage cancers. Population and incidence inputs were obtained from nation-specific sources, while efficacy and quality of life data were informed by the individual trials. Productivity outcomes were estimated using a human capital approach.ResultsBetween 2023 and 2032, 57,075 (60.4%) of 94,426 patients with early-stage cancers eligible for adjuvant or perioperative treatment are estimated to receive anti-PD-1 agents. This was associated with an increase in total life years (8,878, 2.4%), quality-adjusted life-years (9,029, 3.1%), and event-/disease-/recurrence-free life years (25,149, 9.0%), and a reduction in progression events or recurrences (6,839, 16.8%), active metastatic treatments (4,845, 14.0%), and deaths (3,013, 16.2%). The clinical benefits also resulted in a gain in productive years (20,717, 17.6%).ConclusionThe use of anti-PD-1 agents in adjuvant or perioperative settings can lead to substantial health and productivity gains. Effective planning and investment are needed for timely access to these agents for patients.